Negative pole piece, sodium ion battery and electric device
By adjusting the particle size distribution of hard carbon particles and the structural parameters of the negative electrode sheet, the polarization problem of sodium-ion batteries during high-current charge and discharge is solved, the power input and output performance is improved, and the cycle stability is improved.
Patent Information
- Application Number
- CN202310882834.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
Sodium ion batteries face problems such as poor rate performance and insufficient power output capability, especially when charging and discharging large currents, which can easily lead to polarization of the negative electrode material, affecting the cycle stability of the battery.
By adjusting the volume average particle size of hard carbon particles to satisfy 0.8≤(Dv90-Dv50)/Dv10≤5, combined with appropriate compaction density and porosity and tortuosity control of the negative electrode piece, a sodium ion diffusion method is established Appropriate path to reduce the polarization effect of large current on the negative electrode material.
It improves the power input and output performance of sodium-ion batteries, increases the cycle stability and energy density of the battery, and solves the problems of poor rate performance and insufficient power output capability.
Smart Images

Figure CN119340328A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a negative electrode plate, a sodium ion battery and an electrical device. Background Art
[0002] As the application of lithium-ion battery technology in consumer electronics, electric vehicles, energy storage and other markets gradually expands, the problem of insufficient lithium resources has also begun to emerge. Sodium batteries have gradually attracted attention due to their abundant reserves of sodium elements, and have an important strategic position in application fields with high cost requirements such as energy storage. Secondly, sodium batteries have higher conductivity than lithium batteries under the same electrolyte concentration, which further reduces production costs.
[0003] Hard carbon materials have a large interlayer spacing and a disordered microcrystalline structure, which makes them conducive to the insertion and extraction of sodium ions. They are recognized by the industry as the most mature and commercially promising negative electrode materials. However, they still face technical problems such as poor rate performance and insufficient power output capacity. Summary of the invention
[0004] In view of the above problems, the present application provides a negative electrode plate, a sodium ion battery and an electrical device, which can improve the power input performance of the sodium ion battery while also increasing the output power of the battery.
[0005] In a first aspect, the present application provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode material located on at least one side of the negative electrode current collector, wherein the negative electrode material comprises hard carbon particles, and the volume average particle size of the hard carbon particles satisfies: 0.8≤(Dv90-Dv50) / Dv10≤5.
[0006] The present application selects to adjust the volume average particle size of the hard carbon particles to satisfy 0.8≤(Dv90-Dv50) / Dv10≤5, which can not only reduce the migration distance of sodium ions in the ion channel and thus improve the high-current charging and discharging of the battery, but also control the polarization problem of the negative electrode material caused by high-current charging and discharging. If the volume average particle size of the hard carbon particles is adjusted to be less than 0.8, although the migration path of sodium ions between particles is improved, the high current is likely to cause polarization of the pole piece. On the contrary, if the volume average particle size of the hard carbon particles is adjusted to be greater than 5, it is not conducive to improving the migration path of sodium ions between particles.
[0007] In some embodiments of the present application, the volume average particle size of the hard carbon particles satisfies: 1≤(Dv90-Dv50) / Dv10≤4.
[0008] The present application further selects to adjust the volume average particle size of the hard carbon particles to satisfy 1≤(Dv90-Dv50) / Dv10≤4, which is relatively beneficial to improving the power input and output performance of the sodium ion battery while making it easier to adjust the particle homogenization process.
[0009] In some embodiments of the present application, the volume average particle size of the hard carbon particles satisfies: 1.3≤(Dv90-Dv50) / Dv10≤3.6.
[0010] In the experimental study, the present application further selected the hard carbon particles to have a volume average particle size that satisfies: 1.3≤(Dv90-Dv50) / Dv10≤3.6, so that the hard carbon particles are more uniform.
[0011] In some embodiments of the present application, the volume average particle size of the hard carbon particles satisfies one or more of the following combinations:
[0012] (1.1) Dv90 is 10 μm to 19 μm; preferably 12.5 μm to 18 μm;
[0013] (1.2) Dv50 is 5 μm to 9.9 μm; preferably 7.2 μm to 9.5 μm;
[0014] (1.3) Dv10 is 1.5 μm to 4.9 μm; preferably 1.5 μm to 2.9 μm or 3.1 μm to 4.5 μm.
[0015] In the present application, the volume average particle size of the hard carbon particles affects the porosity and tortuosity of the negative electrode plate. At the same time, a certain negative electrode plate porosity and tortuosity in turn determine the volume average particle size of the hard carbon particles. By selecting hard carbon particles with a suitable particle size, it is beneficial to establish a suitable path for sodium ion diffusion and reduce the impact of large current charging and discharging on the polarization of the negative electrode material.
[0016] In some embodiments of the present application, the compaction density of the negative electrode material is 0.8 g / cm 3 ~1.2g / cm 3 .
[0017] In some embodiments of the present application, the compaction density of the negative electrode material is 0.9 g / cm 3 ~1.1g / cm 3 .
[0018] In some embodiments of the present application, the compaction density of the negative electrode material is 0.95 to 1.05 g / cm 3 .
[0019] In this application, the compaction density has a great influence on the battery performance. For example, the compaction density is closely related to the specific capacity, internal resistance and battery cycle performance of the negative electrode material. The specific value of the compaction density is affected by the ratio between large particles and small particles. In turn, the difference in compaction density directly changes the distance and gap between large and small particles. If the compaction density of this application is greater than 1.2g / cm3 , which will inevitably affect the distance and gap between large and small particles. If the compaction density is less than 0.8g / cm 3 , which will affect the energy density of the negative electrode material. Therefore, the present application has experimentally explored that the negative electrode material that meets this range of values is relatively beneficial for improving the power input and output performance of the sodium ion battery.
[0020] In some embodiments of the present application, the negative electrode current collector is provided with a through hole, and the through hole satisfies one or more of the following combinations:
[0021] (2.1) The centers of the through holes distributed along the length direction of the negative electrode current collector are not in the same straight line;
[0022] (2.2) The shape of the through hole includes a circle or a polygon;
[0023] (2.3) The through hole has a diameter of 100 μm to 1000 μm, preferably 200 μm to 500 μm.
[0024] In the present application, the design of through holes can reduce the internal resistance and increase the electron conduction path. The selection of polygonal through holes can also increase the contact area between the negative electrode material and the current collector, indirectly increasing the adhesion between the negative electrode material and the current collector. The enhanced adhesion can also further reduce the internal resistance value.
[0025] In some embodiments of the present application, the tortuosity of the negative electrode sheet is T, and the porosity of the negative electrode sheet is β, satisfying: 16.1≤T / β≤23.3.
[0026] In some embodiments of the present application, the following is satisfied: 16.5≤T / β≤23.0.
[0027] In this application, since the electrolyte is filled in the pores of the negative electrode sheet, the sodium ions are conducted through the electrolyte in the pores, and the conductivity characteristics of the sodium ions are closely related to the porosity and tortuosity. Generally, the greater the porosity, the lower the tortuosity, the higher the volume fraction of the electrolyte phase, the more complete the electrolyte infiltration, and the greater the effective sodium ion conductivity. However, this will inevitably affect the content of hard carbon particles in the negative electrode sheet and lead to a low content of hard carbon particles, thereby affecting the energy density of the sodium ion battery. Therefore, this application chooses to control the tortuosity and porosity of the negative electrode material within a certain ratio range, such as 16.1≤T / β≤23.3. Within this range, combined with the compaction density of the negative electrode material, the impact on the energy density of the sodium ion battery is minimized as much as possible while improving the sodium ion conduction characteristics.
[0028] In some embodiments of the present application, the negative electrode plate satisfies one or both of the following:
[0029] (3.1) The tortuosity T of the negative electrode sheet satisfies 9.5 to 10.5, preferably 9.8 to 10.3;
[0030] (3.2) The porosity β of the negative electrode sheet satisfies 45% to 59%, preferably 50% to 55%.
[0031] The present application selects a hard carbon material with a suitable particle size to form it on the surface of the negative electrode current collector and sets a certain compaction density, and finally measures that the tortuosity T satisfies 9.5 to 10.5 and the porosity β satisfies 45% to 59%.
[0032] The second aspect of the present application is to provide a sodium ion battery, comprising:
[0033] Positive electrode sheet: comprising a positive electrode current collector and a positive electrode material located on at least one side of the positive electrode current collector;
[0034] The negative electrode sheet of the first aspect;
[0035] Separator: located between the positive electrode sheet and the negative electrode sheet;
[0036] Electrolyte.
[0037] The sodium ion battery provided in the present application alleviates the problems of poor rate performance and insufficient power output capacity, and is conducive to improving the power input and output performance of the sodium ion battery.
[0038] In some embodiments of the present application, the thickness of the positive electrode sheet is H1, the thickness of the negative electrode sheet is H2, and each thickness satisfies one or more of the following combinations:
[0039] (4.1) H1 / H2 satisfies: 0.34 to 1.46, preferably 0.5 to 1.125;
[0040] (4.2) H1 is 90 μm to 190 μm, preferably 110 μm to 180 μm;
[0041] (4.3) H2 is 130 μm to 260 μm, preferably 160 μm to 220 μm.
[0042] In this application, since sodium ions are constantly being extracted and embedded between the positive and negative electrodes, by controlling the thickness between the positive and negative electrode sheets to meet this range, it is possible to effectively control the sodium ion transmission path and reduce the probability of the negative electrode material being polarized. This application selects a ratio between H1 and H2 that satisfies 0.34 to 1.46, which is beneficial for shortening the path of sodium ions being extracted from the positive electrode and embedded in the negative electrode, and can also improve the extraction time of sodium ions from the positive electrode and the embedding time of sodium ions in the negative electrode, thereby improving the polarization degree of the negative electrode while reducing the time difference between the two.
[0043] In some embodiments of the present application, the electrolyte satisfies one or more of the following combinations:
[0044] (5.1) The viscosity at room temperature is 2.0 mPa.s to 5.0 mPa.s, preferably 2.5 mPa.s to 4.0 mPa.s;
[0045] (5.2) The electrical conductivity at room temperature is 8.0 mS / cm to 15 mS / cm, preferably 10 mS / cm to 15 mS / cm.
[0046] The present application selects hard carbon particles whose volume average particle size satisfies: 0.8≤(Dv90-Dv50) / Dv10≤5. At this particle size, the pores between the negative electrode material particles are enlarged. Combined with the use of the low-viscosity and high-conductivity electrolyte protected by the present application, it is beneficial for the electrolyte to quickly infiltrate into the pores and provide a sodium ion migration channel. The migration rate of sodium ions in the migration channel is also improved, further improving the battery's kinetic performance.
[0047] The third aspect of the present application is to provide an electrical device comprising the negative electrode plate described in the first aspect or the sodium ion battery described in the second aspect.
[0048] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0050] Figure 1 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;
[0051] Figure 2 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;
[0052] Figure 3 This is a schematic diagram of the structure of the negative electrode sheet of some embodiments of the present application;
[0053] Figure 4 This is a schematic diagram of the structure of the negative electrode current collector of some embodiments of the present application;
[0054] Figure 5 This is a schematic diagram of the structure of the negative electrode current collector of some embodiments of the present application;
[0055] Figure 6 A schematic diagram of the tortuosity of the negative electrode sheet in some embodiments of the present application;
[0056] The reference numerals in the specific implementation manner are as follows:
[0057] 10000, vehicles;
[0058] 1000, battery; 2000, controller; 3000, motor;
[0059] 100. Single cell;
[0060] 200, box body; 210, first part; 220, second part;
[0061] 110. Negative electrode plate; 111. Negative electrode current collector; 112. Negative electrode material; 120. Through hole.
[0062] Coordinate axis x direction: length direction of negative electrode current collector;
[0063] Coordinate axis y direction: width direction of negative electrode current collector;
[0064] Coordinate axis z direction: thickness direction of negative electrode current collector. DETAILED DESCRIPTION
[0065] Below, the embodiments of the negative electrode plate, sodium ion battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0066] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0067] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0068] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0069] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0070] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0071] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0072] If not otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0073] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).
[0074] Unless otherwise specified, the orientations or positional relationships indicated by technical terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application.
[0075] Summary of the main line of invention:
[0076] The content of lithium in the earth's crust is only 0.0065%, while the content of sodium in the earth's crust is as high as 2.64%. Compared with lithium-ion batteries composed of scarce elements such as lithium, cobalt, and nickel, sodium batteries have a natural advantage in cost. Hard carbon negative electrode materials have structural characteristics of complex microstructure, high defects, and high porosity, which support the sodium storage mechanism of intercalation and adsorption; its large interlayer spacing and disordered microcrystalline structure make it easier for sodium ions to embed and detach. It is recognized by the industry as the most mature and commercially promising negative electrode material, but it still faces technical problems such as poor rate performance and insufficient power output capacity.
[0077] In order to solve the above technical problems, the prior art discloses that in the preparation process of hard carbon materials, the pore structure, interlayer spacing, etc. of hard carbon are controlled by regulating the microstructure during the synthesis or pyrolysis of the precursor or by adopting various methods such as coating, composite, and heteroatom doping with other materials. Although this can improve the rate performance of the battery, etc., due to the limitation of the manufacturing cost of hard carbon materials, the current control methods have not been clearly and uniformly recognized.
[0078] Due to the limitations of the preparation process of hard carbon materials, the particle size distribution range of hard carbon materials is relatively wide, generally ranging from a few microns to tens of microns. The uneven particle size distribution may affect the interlayer spacing or pore structure of the material. If a hard carbon material with good particle size distribution characteristics can be obtained, and the kinetic performance of the hard carbon material corresponding to the sodium ion battery can be further explored, it will be beneficial to the existing sodium ion battery research.
[0079] Based on the above considerations, in order to solve the kinetic performance problems faced by sodium ion batteries, such as poor rate performance and insufficient power output capacity, the applicant has obtained a negative electrode sheet, a sodium ion battery and an electrical device according to the above design concept and related experimental research.
[0080] First, the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode material located on at least one side of the negative electrode collector. The negative electrode material includes hard carbon particles, and the volume average particle size of the hard carbon particles satisfies: 0.8≤(Dv90-Dv50) / Dv10≤5.
[0081] The present application adjusts the particle size distribution of the hard carbon particles to make them uniform. Specifically, for example, the ratio between large particles and small particles is adjusted to ensure that there is enough gap between large and small particles to provide an ion channel in which sodium ions can shuttle smoothly. The present application chooses to adjust the volume average particle size of the hard carbon particles to meet 0.8≤(Dv90-Dv50) / Dv10≤5, which can not only reduce the migration distance of sodium ions in the ion channel and thus improve the high-current charging and discharging of the battery, but also control the polarization of the negative electrode material caused by the high-current charging and discharging, thereby improving the cycle stability of the battery. If the volume average particle size of the hard carbon particles is adjusted to be less than 0.8, although the migration path of sodium ions between particles is improved, the large current is likely to cause polarization of the pole piece. On the contrary, if the volume average particle size of the hard carbon particles is adjusted to be greater than 5, it is not conducive to improving the migration path of sodium ions between particles.
[0082] Therefore, the negative electrode plate provided in the present application is applied to sodium ion batteries to alleviate the problems of poor rate performance and insufficient power output capacity, which is beneficial to improving the power input and output performance of sodium ion batteries. The negative electrode plate provided in the present application is applied to sodium ion batteries, which can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is applied to the power field, such as mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but not limited to the above fields.
[0083] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.
[0084] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.
[0085] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.
[0086] Please refer to Figure 2 , Figure 2 The exploded diagram of the battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a single cell 100. Conventional single cells include primary cells or secondary cells. The present application specifically protects secondary cells. The single cell 100 is contained in the housing 200. The housing 200 is used to provide a containing space for the single cell 100. The housing 200 can adopt a variety of structures.
[0087] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.
[0088] In the battery 1000, there may be multiple single cells 100, and the multiple single cells 100 may be connected in series, in parallel, or in mixed connection. Mixed connection means that the multiple single cells 100 are both connected in series and in parallel. The multiple single cells 100 may be directly connected in series, in parallel, or in mixed connection, and then the whole formed by the multiple single cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple single cells 100 in series, in parallel, or in mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in mixed connection to form a whole, and then accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple single cells 100.
[0089] The single cell 100 includes but is not limited to a sodium ion battery, and the single cell 100 may be cylindrical, flat, rectangular, or in other shapes.
[0090] like Figure 3 As shown, the present application discloses a negative electrode plate 110 in some embodiments, wherein the negative electrode plate 110 comprises a negative electrode current collector 111 and a negative electrode material 112 located on at least one side surface of the negative electrode current collector 111, wherein the negative electrode material 112 comprises hard carbon particles, wherein the volume average particle size of the hard carbon particles satisfies: 0.8≤(Dv90-Dv50) / Dv10≤5.
[0091] The hard carbon of the present application includes products obtained by any conventional preparation method in the art or provided by any supplier, such as biomass-based hard carbon (obtained by heat treatment of biomass) or organic polymer-based hard carbon (such as obtained by artificial synthesis); at the same time, hard carbon also includes materials formed by various methods such as coating, composite, and heteroatom doping with other materials, such as composite conductive materials on the surface of hard carbon particles, which conductive materials include conductive carbon, carbon nanotubes or graphene, etc., to improve the conductivity of the hard carbon material and ultimately increase the charge and discharge current; the coating, composite and doping methods of the present application include any conventional forms in the art.
[0092] The average volume distribution particle size Dv50 of the present application refers to the particle size corresponding to the cumulative volume distribution percentage of hard carbon particles reaching 50%. Similarly, the average volume distribution particle size Dv90 refers to the particle size corresponding to the cumulative volume distribution percentage of hard carbon particles reaching 90%. The average volume distribution particle size Dv10 refers to the particle size corresponding to the cumulative volume distribution percentage of hard carbon particles reaching 10%. In the present application, each average volume distribution particle size can be measured by laser diffraction particle size analysis, or by other methods. When laser diffraction particle size analysis is used, the standard GB / T19077-2016 can be referred to, and a laser particle size analyzer (such as MalvernMaster Size 3000) can be used. The " / " that appears in the particle size distribution relationship of the present application includes a division relationship.
[0093] The present application includes a method of forming a negative electrode material 112 on one side surface or on more than two sides of a negative electrode current collector 111. The diagram of the present application schematically shows that the negative electrode material 112 is formed on both side surfaces of the negative electrode current collector 111, and the method of forming the negative electrode material on the negative electrode current collector includes any conventional method in the art, such as coating, deposition, etc.
[0094] In the present application, the volume average particle size of the hard carbon particles is adjusted to meet 0.8≤(Dv90-Dv50) / Dv10≤5, which can not only reduce the migration distance of sodium ions in the ion channel and thus improve the high-current charging and discharging of the battery, but also control the problem of polarization of the negative electrode material caused by high-current charging and discharging. Therefore, the sodium ion battery provided in the present application alleviates the problems of poor rate performance and insufficient power output capacity, which is conducive to improving the power input and output performance of the sodium ion battery. Among them, the volume average particle size of the hard carbon particles satisfies any one of 0.8, 0.9, 1.0, 1.1, 1.2, 1.5, 1.7, 2.0, 2.1, 2.2, 2.5, 2.7, 3.0, 3.1, 3.2, 3.5, 3.7, 4.0, 4.1, 4.2, 4.5, 4.7, 5.0 or any one of the values in this range.
[0095] According to some embodiments of the present application, the volume average particle size of the hard carbon particles satisfies 1≤(Dv90-Dv50) / Dv10≤4.
[0096] In the present application, when the volume average particle size of the hard carbon particles is adjusted to satisfy 1≤(Dv90-Dv50) / Dv10≤4, it is relatively beneficial to improve the power input and output performance of the sodium ion battery under the premise that it is easier to adjust the particle homogenization process.
[0097] According to some embodiments of the present application, the volume average particle size of the hard carbon particles satisfies: 1.3≤(Dv90-Dv50) / Dv10≤3.6.
[0098] The hard carbon particles of the present application are more uniform under this particle size distribution, which is more conducive to improving the power input and output performance of the sodium ion battery.
[0099] According to some embodiments of the present application, the volume average particle size Dv90 of the hard carbon particles is 10 μm to 19 μm. The volume average particle size Dv90 of the hard carbon particles is any one of 10 μm, 10.5 μm, 11 μm, 12.5 μm, 13 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, and 19 μm, or any one of the values within the range.
[0100] According to some embodiments of the present application, the volume average particle size Dv90 of the hard carbon particles is 12.5 μm to 18 μm.
[0101] According to some embodiments of the present application, the volume average particle size Dv50 of the hard carbon particles is 5 μm to 9.9 μm. The volume average particle size Dv50 of the hard carbon particles is any one of 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, and 9.9 μm, or any one of the values within the range.
[0102] According to some embodiments of the present application, the volume average particle size Dv50 of the hard carbon particles is 7.2 μm to 9.5 μm.
[0103] According to some embodiments of the present application, the volume average particle size Dv10 of the hard carbon particles is 1.5 μm to 4.9 μm. The volume average particle size Dv10 of the hard carbon particles is any one of 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 4.9 μm or any one of the values within the range.
[0104] According to some embodiments of the present application, the volume average particle size Dv10 of the hard carbon particles is 1.5 μm to 2.9 μm.
[0105] According to some embodiments of the present application, the volume average particle size Dv10 of the hard carbon particles is 3.1 μm to 4.5 μm.
[0106] In the present application, the volume average particle size of the hard carbon particles affects the porosity and tortuosity of the negative electrode plate. By selecting hard carbon particles with a suitable particle size, it is helpful to establish a suitable path for sodium ion diffusion and ultimately improve the power input and output functions of the sodium ion battery.
[0107] The present application chooses to mix hard carbon particles with Dv90 of 12.5μm~18μm, Dv50 of 7.2μm~9.5μm, and Dv10 of 1.5μm~2.9μm, or to mix hard carbon particles with Dv90 of 12.5μm~18μm, Dv50 of 7.2μm~9.5μm, and Dv10 of 3.1μm~4.5μm, so as to establish a relatively ideal sodium ion diffusion path and improve the power input and output functions of the sodium ion battery.
[0108] According to some embodiments of the present application, the compaction density of the negative electrode material is 0.8 g / cm 3 ~1.2g / cm 3 Among them, the compaction density of the negative electrode material is 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 Any one of the values or any one of the values that satisfy the range.
[0109] The compaction density in this application includes any conventional meaning in this field, which can be obtained by direct calculation in the design of sodium ion batteries. The compaction density has a great influence on the battery performance. For example, the compaction density is closely related to the specific capacity, internal resistance and battery cycle performance of the negative electrode material, and the specific value of the compaction density is affected by the ratio between large particles and small particles. In turn, the difference in compaction density directly changes the distance and gap between large and small particles. This application chooses to further limit the compaction density under the condition of adjusting the volume average particle size of the hard carbon particles to meet 0.8≤(Dv90-Dv50) / Dv10≤5, so as to achieve sodium ion batteries with high rate charge and discharge and good cycle stability.
[0110] According to some embodiments of the present application, the compaction density of the negative electrode material is 0.9 g / cm 3 ~1.1g / cm 3 .
[0111] In the present application, the negative electrode material that meets the compaction density can take into account the excellent performance of sodium ion batteries in all aspects.
[0112] According to some embodiments of the present application, the compaction density of the negative electrode material is 0.95 g / cm 3 ~1.05g / cm 3 .
[0113] In the present application, the negative electrode material that meets the compaction density can better exert its high-rate charge and discharge performance.
[0114] The negative electrode material in the present application includes but is not limited to hard carbon particles, and also includes other ingredients such as conductive agents, binders, etc., and the amount ratio between the components in the negative electrode material includes any conventional form in the art. For example, the conductive agent includes but is not limited to conductive carbon black, graphite, carbon fiber, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, fullerene, etc., and the binder includes but is not limited to polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, sodium polyacrylate, sodium polyacrylate, polytetrafluoroethylene, polyimide, polyurethane, etc.
[0115] According to some embodiments of the present application, Figure 4 , Figure 5 As shown in FIG. 1 , the negative electrode current collector 111 is provided with through holes 120, and the through holes 120 are arranged along the length direction and the width direction of the negative electrode current collector 111. Figure 4 It can be seen that the length direction of the negative electrode current collector 111 is the coordinate axis x direction, and the width direction of the negative electrode current collector 111 is the coordinate axis y direction. In order to reduce the tearing of the pole piece caused by excessive concentration of through holes due to stretching in the coordinate axis x direction, the present application selects that the centers of the through holes distributed along the coordinate axis x direction are not in the same straight line, and can also be expressed by the distance between two adjacent through holes. For example, the distance between two adjacent through holes distributed along the coordinate axis x direction is a, and the distance between two adjacent through holes distributed along the coordinate axis y direction is b, then b<a is satisfied in numerical value. The distance between two adjacent through holes can be measured by conventional measurement methods known in the art, such as scanning electron microscope instrument testing. As an example, the test can be performed according to the following steps: mark the through holes with a scanning electron microscope, take the distance between the centers of two adjacent through holes as the distance between adjacent through holes, and measure the distance.
[0116] The present application selects the above-mentioned arrangement of through holes to set up, which can also reduce the stress effect of the negative electrode material on the negative electrode plate.
[0117] According to some embodiments of the present application, the shape of the through hole can be any shape conventional in the art, such as a circular through hole or a polygonal through hole, and the polygonal through hole includes a polygonal through hole with more than three sides, such as a pentagon, a five-pointed star, a six-pointed star, a seven-pointed star, etc., wherein the design of the through hole can reduce the internal resistance and increase the electron conduction path, and the selection of a polygonal through hole can also increase the contact area between the negative electrode material and the current collector, and indirectly increase the adhesion between the negative electrode material and the current collector and further reduce the internal resistance. The aperture of the through hole includes any conventional value in the art, such as a micron-level aperture. The aperture of the through hole selected in the present application is between 100μm and 1000μm. If it is greater than 1000μm, it is not conducive to the combination between the negative electrode current collector and the hard carbon particles. If it is less than 100μm, it is not conducive to reducing the internal resistance. The present application further selects the aperture of the through hole to be between 200 μm and 500 μm. Within this range, it is beneficial to increase the adhesion between the negative electrode material and the current collector, and effectively reduce the internal resistance to increase the electron conduction path. In addition, the through hole is formed in any conventional form in the art, such as using a punching device to perform laser punching, etc. The aperture of the through hole can be determined according to the selection of the punching device.
[0118] The negative electrode current collector material of the present application includes but is not limited to at least one of a metal material, a metal alloy material, and a composite material of a metal or a metal alloy and a polymer. As an example, the metal material may be at least one of nickel, copper, aluminum, titanium, silver, and gold. As an example, the metal alloy material may be an alloy formed by adding at least one element of tungsten, platinum, iron, cobalt, magnesium, zinc, and chromium to the above-mentioned metal material. As an example, the composite material of a metal or a metal alloy and a polymer may include a polymer layer and a metal layer or a metal alloy layer disposed on at least one surface of the polymer layer; the polymer layer may include at least one of a thermosetting resin, a thermoplastic resin, a polyester resin, a polyimide resin, and a condensation polymer; the metal layer may include at least one of the above-mentioned metal materials; the metal alloy layer may include at least one of the above-mentioned metal alloy materials.
[0119] According to some embodiments of the present application, the tortuosity of the negative electrode material is T, the porosity of the negative electrode material is β, and 16.1≤T / β≤23.3 is satisfied.
[0120] In this application, if Figure 6As shown, the tortuosity is the ratio of the actual path length Lt of the substance through the porous medium to the medium distance (thickness) L0. In the negative electrode plate, Lt is the actual path length of the sodium ions passing through the negative electrode hard carbon particles, and L0 is the thickness of the layer formed by the negative electrode material. The tortuosity of the negative electrode material can be measured by any conventional method in the art, such as mercury intrusion, etc. Specifically, for example, a measuring instrument: pore size analyzer (such as poremaster60GT) is used and measured in accordance with the standard GB / T21650.1-2008. The specific calculation formula is as follows:
[0121] τ=(2.23-1.13Vρ Hg )(0.92y) 1+E ;
[0122] Among them, y satisfies:
[0123] V: mercury volume; ρ Hg : mercury density; S: total area of the negative electrode;
[0124] △V i : Pore volume change; D i : average pore size; E: porosity index.
[0125] The porosity in this application includes any conventional meaning in the art. This application includes the volume fraction of pores in the negative electrode material. The methods for obtaining the porosity include theoretical estimation, image analysis, mercury injection measurement, etc. This application chooses to obtain it by image analysis. Specifically, photos of the negative electrode sheet are obtained by experimental means such as SEM and X-ray tomography, and the porosity is calculated by processing the photos.
[0126] In this application, since the electrolyte is filled in the pores of the negative electrode sheet, the sodium ions are conducted through the electrolyte in the pores, and the conduction characteristics are closely related to the porosity and tortuosity. Generally, the greater the porosity, the lower the tortuosity, the higher the volume fraction of the electrolyte phase, the more complete the electrolyte infiltration, and the greater the effective sodium ion conductivity. However, this will inevitably affect the content of hard carbon particles in the negative electrode sheet and lead to a low content of hard carbon particles, thereby affecting the energy density of the sodium ion battery. Therefore, this application chooses to control the tortuosity and porosity of the negative electrode material within a certain ratio range, such as 16.1≤T / β≤23.3. Within this range, combined with the compaction density of the negative electrode material, the impact on the energy density of the sodium ion battery is minimized under the premise of improving the sodium ion conduction characteristics.
[0127] According to some embodiments of the present application, the tortuosity T of the negative electrode material and the porosity β of the negative electrode material satisfy: 16.5≤T / β≤23.0.
[0128] The tortuosity T of the negative electrode material of the present application and the porosity β of the negative electrode material satisfy the condition of 16.5≤T / β≤23.0, which is relatively superior to improving the sodium ion conduction characteristics. At the same time, the impact on the energy density of the sodium ion battery is relatively low.
[0129] According to some embodiments of the present application, the tortuosity T of the negative electrode material satisfies 9.5 to 10.5, wherein the tortuosity T of the negative electrode material satisfies any one of 9.5, 9.6, 9.7, 9.8, 9.9, 10, and 10.5 or satisfies any one of the values in the range.
[0130] In the present application, a hard carbon material with a suitable particle size is selected to be formed on the surface of the negative electrode current collector and a certain compaction density is set, and finally the tortuosity T is measured to meet 9.5 to 10.5.
[0131] According to some embodiments of the present application, the tortuosity T of the negative electrode material satisfies 9.8 to 10.3.
[0132] The tortuosity T of the negative electrode material selected in the present application satisfies 9.8 to 10.3, which is conducive to establishing a suitable path for the diffusion of sodium ions and ultimately improving the power input and output functions of the sodium ion battery.
[0133] According to some embodiments of the present application, the porosity β of the negative electrode material satisfies 45% to 59%, wherein the porosity β of the negative electrode material satisfies any one of 45%, 50%, 55%, 59% or any one of the values in the range.
[0134] In the present application, a hard carbon material with a suitable particle size is selected to be formed on the surface of the negative electrode current collector and a certain compaction density is set, and finally the measured porosity β satisfies 45% to 59%.
[0135] According to some embodiments of the present application, the porosity β of the negative electrode material satisfies 50% to 55%.
[0136] The porosity β of the negative electrode material selected in the present application satisfies 50% to 55%, which is conducive to establishing a suitable path for the diffusion of sodium ions and ultimately improving the power input and output functions of the sodium ion battery.
[0137] The second aspect of the present application is to provide a sodium ion battery, which comprises a positive electrode plate, a negative electrode plate described in the first aspect, a separator between the positive electrode plate and the negative electrode plate, and an electrolyte.
[0138] According to some embodiments of the present application, the thickness of the positive electrode sheet is H1, the thickness of the negative electrode sheet is H2, and the ratio between H1 and H2 satisfies: 0.34 to 1.46. The ratio between H1 and H2 satisfies any one of 0.34, 0.50, 0.60, 0.70, 0.80, 0.90, 1.0, 1.1, 1.2, 1.3, 1.4, and 1.46 or any one of the values in the range.
[0139] In the present application, the thickness of the positive electrode sheet and the negative electrode sheet refers to the distance between one end face of the electrode sheet and the other end face arranged away from the end face, which can be obtained by direct measurement, such as using a thickness gauge or a micrometer. Since sodium ions are constantly escaping and embedding between the positive and negative electrodes, by controlling the thickness between the positive and negative electrode sheets to meet this range of values, it is possible to effectively control the sodium ion transmission path and reduce the probability of the negative electrode material being polarized. The present application selects a ratio between H1 and H2 that satisfies 0.34 to 1.46, which is conducive to shortening the path of sodium ions escaping from the positive electrode and embedding in the negative electrode, and can also improve the sodium ion escaping time at the positive electrode and embedding time at the negative electrode, and improve the polarization degree of the negative electrode while reducing the difference between the two times.
[0140] According to some embodiments of the present application, the ratio between H1 and H2 satisfies: 0.5-1.125.
[0141] The ratio between H1 and H2 in the present application satisfies 0.5 to 1.125, which is conducive to establishing a suitable path for sodium ion diffusion while improving the polarization degree of the negative electrode, and ultimately achieving improved power input and output functions of the sodium ion battery.
[0142] According to some embodiments of the present application, H1 is 90 μm to 190 μm.
[0143] According to some embodiments of the present application, H1 is 110 μm to 180 μm.
[0144] According to some embodiments of the present application, H2 is 130 μm to 260 μm.
[0145] According to some embodiments of the present application, H2 is 160 μm to 220 μm.
[0146] In the specific embodiments, the present application has explored in detail the influence of the thickness of the positive and negative electrode sheets on the power input and output functions of the sodium ion battery. The thickness of the positive and negative electrode sheets that meets the protection scope of the present application is relatively superior to improving the power performance of the sodium ion battery.
[0147] According to some embodiments of the present application, the viscosity of the electrolyte at room temperature is 2.0 mPa.s to 5.0 mPa.s.
[0148] According to some embodiments of the present application, the viscosity of the electrolyte at room temperature is 2.5 mPa.s to 4.0 mPa.s.
[0149] According to some embodiments of the present application, the conductivity of the electrolyte at room temperature is 8.0 mS / cm to 15 mS / cm.
[0150] According to some embodiments of the present application, the conductivity of the electrolyte at room temperature is 10 mS / cm to 15 mS / cm.
[0151] The present application selects hard carbon particles whose volume average particle size satisfies: 0.8≤(Dv90-Dv50) / Dv10≤5. At this particle size, the pores between the negative electrode material particles are enlarged. Combined with the use of the low-viscosity and high-conductivity electrolyte protected by the present application, it is beneficial for the electrolyte to quickly infiltrate into the pores and provide a sodium ion migration channel. The migration rate of sodium ions in the migration channel is also improved, further improving the battery's kinetic performance.
[0152] The electrolyte in the present application includes sodium salt, organic solvent and additive, wherein the organic solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and methyl tert-butyl ether, and the present application selects one or two combinations of ester solvents or ether solvents. The sodium salt can be a sodium salt commonly used in the art for electrolyte. As an example, the sodium salt can be selected from at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride. The present application selects one or two of sodium hexafluorophosphate and sodium tetrafluoroborate. Additives include but are not limited to film-forming additives, and the present application selects one or two of fluoroethylene carbonate or vinylene carbonate.
[0153] According to some embodiments of the present application, the positive electrode current collector may be a metal foil or a composite current collector, wherein the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0154] According to some embodiments of the present application, the positive electrode material in the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes but is not limited to sodium transition metal oxides, polyanionic compounds, Prussian blue compounds, etc., wherein the transition metal in the sodium transition metal oxide can be one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce, and the sodium transition metal oxide is, for example, Na x MO 2 , wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1. Polyanionic compounds include sodium vanadium trifluorophosphate (Na 3 V 2 (PO 4 ) 2 F 3 ), sodium vanadium fluorophosphate (NaVPO 4 F), sodium vanadium phosphate (Na 3 V 2 (PO 4 ) 3 ), Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 、NaFePO 4 Prussian blue compounds are Na x M 1 M 2 (CN) 6 , where M 1 、M 2 It is one or more of Fe, Mn, Co, Ni, Cu, Zn, Cr, Ti, V, Zr, and Ce, wherein 0<x≤2.
[0155] A binder and / or a conductive agent may also be added to the positive electrode active material, and the types of the binder and the conductive agent are not limited, and those skilled in the art may select them according to actual needs. For example, the binder may be one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), and styrene-butadiene rubber (SBR), and the conductive agent may be one or more of graphite, superconducting carbon, acetylene black, carbon black, carbon nanotubes, graphene, and carbon nanofibers.
[0156] According to some embodiments of the present application, the isolation membrane is arranged between the positive electrode plate and the negative electrode plate to prevent the positive and negative electrodes from short-circuiting. The isolation membrane can be a base membrane, or a composite membrane formed by a base membrane and a surface coating on at least one side of the base membrane. The material of the base membrane includes but is not limited to any conventional material in the art, such as polypropylene, polyethylene, polyimide, polyamide, polyethylene terephthalate, polyvinylidene fluoride or a cellulose substrate, etc. The material of the coating includes but is not limited to any conventional form in the art, for example, the coating includes a film layer formed on the surface of the base film by at least one of inorganic particles, organic particles, and organic-inorganic hybrid particles, and the inorganic particles include but are not limited to boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, aluminum magnesium silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, etc. The organic particles include but are not limited to at least one of polyethylene particles, polypropylene particles, polystyrene particles, polyvinylidene fluoride particles, cellulose, cellulose modifiers (e.g., carboxymethyl cellulose), melamine resin particles, phenolic resin particles, polyester particles (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), silicone resin particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles, polyaryletherketone particles, and copolymers of butyl acrylate and ethyl methacrylate (e.g., cross-linked polymers of butyl acrylate and ethyl methacrylate).
[0157] In order to make the purpose, technical solution and advantages of this application clearer, the negative electrode sheet, sodium ion battery and electrical device protected by this application are described in detail below in combination with specific embodiments. The chemical substances, reagents, etc. used in the following embodiments are all conventional models and manufacturers in the field.
[0158] [Preparation of negative electrode sheet]
[0159] Example 1
[0160] A method for preparing a negative electrode sheet is provided, comprising the following preparation process:
[0161] S1. Hard carbon particles of suitable particle size, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and conductive agent are dispersed uniformly in an appropriate amount of deionized water in a mass ratio of 97:1.2:1.3:0.5 to obtain a negative electrode slurry; wherein the hard carbon particles are from Kuraray of Japan;
[0162] S2, using a punching device to process the copper foil to form a five-pointed star-shaped through hole with a hole diameter of 200 μm to 300 μm;
[0163] S3, coating the negative electrode material evenly on both sides of the copper foil, cold pressing the whole after coating, and cutting to obtain negative electrode sheets.
[0164] Determination of negative electrode related parameters:
[0165] 1. Hard carbon particle size test: Use laser diffraction particle size distribution measuring instrument (Malvem Mastersizer
[0166] 3000), and according to the particle size distribution laser diffraction method GB / T19077-2016, the particle size distribution was measured to obtain Dv50, Dv90 and Dv10.
[0167] 2. Negative electrode sheet compaction density test: Roll the dry negative electrode sheet with a rolling pressure of 1 to 5T, fold it in half three times after rolling, and observe that the crease is not transparent. Under the above conditions, roll the electrode sheet with the maximum pressure it can withstand, test the electrode sheet thickness, and calculate the compaction density = surface density / material thickness, where the surface density is the total mass of negative electrode material contained in the unit area of the negative electrode sheet.
[0168] 3. Negative electrode porosity test: The American McMurraytick true density meter (ACCUPYC II1345) is used to measure the porosity of the electrode by gas displacement method. The percentage of the pore volume in the electrode to the total volume of the electrode is the electrode porosity, and the calculation formula is: P = (V-V0) / V×100%, where V0 is the true volume and V is the apparent volume.
[0169] 4. Negative electrode tortuosity test: Use pore size analyzer (such as poremaster60GT) and refer to standard GB / T21650.1-2008 for measurement. The specific calculation formula is as follows:
[0170] τ=(2.23-1.13Vρ Hg )(0.92y) 1+E ;
[0171] Among them, y satisfies:
[0172] V: mercury volume; ρ Hg : mercury density; S: total area of the negative electrode;
[0173] △V i : Pore volume change; D i : average pore size; E: porosity index.
[0174] The relevant parameters of the negative electrode plate provided in Example 1 are shown in Table 1.
[0175] Table 1 Parameters of negative electrode
[0176]
[0177]
[0178] [Preparation of positive electrode sheet]
[0179] Take Na 3 V 2 (PO 4 ) 2 F 3 The material is a positive electrode (gram capacity 128.3 mAh / g), polyvinylidene fluoride (PVDF) as a binder, and conductive carbon black (Super-P) as a conductive agent, which are mixed uniformly in N-methylpyrrolidone (NMP) solvent at a mass ratio of 90%:5%:5% to prepare a positive electrode slurry. An extrusion coater is used to coat the positive electrode active material per unit area at a mass of 360 mg / 1540.25 cm 2 It is required to coat the positive electrode slurry on the surface of the aluminum foil and dry it, and then use a cold press to press the coated electrode to 2.57g / cm 3 The design is compacted and cold pressed.
[0180] [Preparation of electrolyte]
[0181] NaPF 6 With NaBF 4 (the molar ratio is 1:1) is dissolved in triethylene glycol dimethyl ether and ethylene carbonate (the volume ratio is 1:1) to form a solution with a concentration of 1 mol / L, and then 0.1 wt% of a film-forming additive is added.
[0182] The relevant parameters of the positive electrode plate and the electrolyte provided in Example 1 are shown in Table 2.
[0183] Table 2 Parameters of positive electrode and electrolyte
[0184]
[0185]
[0186] [Isolation film]
[0187] A polyethylene porous membrane having a thickness of 7 μm was selected, and an alumina ceramic coating layer having a thickness of 0.5 μm was formed on two opposite surfaces of the polyethylene porous membrane.
[0188] [Preparation of sodium ion batteries]
[0189] According to some embodiments of the present application, the prepared negative electrode sheet, the isolation membrane and the positive electrode sheet are stacked in order, the isolation membrane is placed between the positive and negative electrode sheets to play an isolating role, and the bare battery cell is wound up, the bare battery cell is baked at 100°C to remove water, and then the electrolyte is injected and sealed, and then the sodium ion battery is obtained through processes such as standing, hot and cold pressing, formation, secondary liquid injection, aging, shaping, and capacity testing.
[0190] [Performance test of sodium ion battery]
[0191] (1) Battery DC pulse resistance (DCR) performance test:
[0192] At 25°C, the sodium-ion battery was fully charged to the upper limit of the operating voltage at 0.5C and then left to stand for 2 hours. It was adjusted to 50% SOC by discharging at a rate of 0.5C. Then, the battery cell was pulse-discharged at a rate of 4.0C for 30 seconds at 25°C, the sodium-ion battery voltage drop ΔU was recorded, and the DC resistance DCR = ΔU / I was calculated.
[0193] (2) Battery rate performance test:
[0194] The sodium-ion battery was fully charged and discharged at 25°C using 0.33C, 0.5C, 1C, 2C, and 3C, and the capacity retention rate at different charge and discharge rates was recorded.
[0195] (3) Battery discharge power test:
[0196] The sodium-ion battery is fully charged to 100% SOC at 25°C, left to stand for 2 hours, then discharged at 0.5C to 50% SOC, and discharged at a constant current of discharge current X for 60 seconds. The voltage just reaches the lower voltage limit (0% SOC), and the power is the maximum discharge power at this time. (The current X is adjusted continuously until it reaches a suitable value, and the voltage just reaches the lower limit after 60 seconds of discharge)
[0197] (4) Battery cycle performance test:
[0198] The sodium ion battery was charged at 0.5C and discharged at 1C at 25°C, and the capacity retention rate of the sodium ion battery after 400 cycles was recorded.
[0199] The specific performance of sodium ion batteries is shown in Table 3;
[0200] Table 3 Battery performance list
[0201]
[0202]
[0203] From Tables 1 to 3, it can be seen that the sodium ion battery disclosed in the embodiments of the present application can be charged and discharged at a large current, and has high cycle stability of charge and discharge, which effectively improves the problem of polarization of the negative electrode material caused by large current charge and discharge, and is beneficial to improving the power input and output performance of the sodium ion battery.
[0204] Comparative Examples 1 to 4 show that if the volume average particle size of the hard carbon particles is not within the protection scope of the present application, the resistance of the sodium ion battery increases rapidly, which is not conducive to the transmission of sodium ions and thus affects the fast charging performance and discharge power of the battery at different rates.
[0205] The sodium ion battery performance illustrated in Comparative Examples 5 to 10 is compared with the sodium ion battery performance illustrated in the embodiment of the present application, which once again proves that sodium ions are conducted through the electrolyte in the pores, and its conduction characteristics are closely related to the porosity and tortuosity of the negative electrode material. If T / β is less than 16.1, it has little effect on the conduction of sodium ions, but it is easy to cause the energy density of the secondary battery to decrease, such as the capacity retention rate of 400 cycles. If T / β is greater than 23.3, it is directly not conducive to the conduction of sodium ions. At the same time, under the condition of satisfying 16.1≤T / β≤23.3, the appropriate compaction density of the negative electrode material and the full and effective infiltration of the appropriate electrolyte will also improve the sodium ion conduction characteristics.
[0206] In summary, the sodium ion battery designed in the present application can improve the power input performance of the sodium ion battery while also increasing the output power of the battery.
[0207] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode material located on at least one side of the negative electrode current collector, characterized in that: The negative electrode material comprises hard carbon particles, characterized in that: the volume average particle size of the hard carbon particles satisfies: 0.8≤(Dv90-Dv50) / Dv10≤5.
2. The negative electrode plate according to claim 1, characterized in that: The volume average particle size of the hard carbon particles satisfies: 1≤(Dv90-Dv50) / Dv10≤4, preferably 1.3≤(Dv90-Dv50) / Dv10≤3.
6.
3. The negative electrode plate according to claim 1, characterized in that: The volume average particle size of the hard carbon particles satisfies one or a combination of two or more of the following: (1.1) Dv90 is 10 μm to 19 μm; preferably 12.5 μm to 18 μm; (1.2) Dv50 is 5 μm to 9.9 μm; preferably 7.2 μm to 9.5 μm; (1.3) Dv10 is 1.5 μm to 4.9 μm; preferably 1.5 μm to 2.9 μm or 3.1 μm to 4.5 μm.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The compaction density of the negative electrode material is 0.8 g / cm 3 ~1.2g / cm 3 , preferably 0.9 g / cm 3 ~1.1g / cm 3 , more preferably 0.95 to 1.05 g / cm 3 .
5. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The negative electrode current collector is provided with through holes, and the through holes satisfy one or more of the following combinations: (2.1) The centers of the through holes distributed along the length direction of the negative electrode current collector are not on the same straight line; (2.2) The shape of the through hole includes a circle or a polygon; (2.3) The through hole has a diameter of 100 μm to 1000 μm, preferably 200 μm to 500 μm.
6. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The tortuosity of the negative electrode plate is T, and the porosity of the negative electrode plate is β, which satisfies: 16.1≤T / β≤23.3, preferably 16.5≤T / β≤23.
0.
7. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The negative electrode plate satisfies one or both of the following: (3.1) The tortuosity T of the negative electrode sheet satisfies 9.5 to 10.5, preferably 9.8 to 10.3; (3.2) The porosity β of the negative electrode sheet satisfies 45% to 59%, preferably 50% to 55%.
8. A sodium ion battery, characterized in that: include: Positive electrode sheet: comprising a positive electrode current collector and a positive electrode material located on at least one side of the positive electrode current collector; The negative electrode sheet according to any one of claims 1 to 7; Separator: located between the positive electrode sheet and the negative electrode sheet; Electrolyte.
9. The sodium ion battery according to claim 8, characterized in that: The thickness of the positive electrode sheet is H1, the thickness of the negative electrode sheet is H2, and each thickness satisfies one or more of the following combinations: (4.1) H1 / H2 satisfies: 0.34 to 1.46, preferably 0.5 to 1.125; (4.2) H1 is 90 μm to 190 μm, preferably 110 μm to 180 μm; (4.3) H2 is 130 μm to 260 μm, preferably 160 μm to 220 μm.
10. The sodium ion battery according to claim 8 or 9, characterized in that: The electrolyte satisfies one or more of the following: (5.1) The viscosity at room temperature is 2.0 mPa.s to 5.0 mPa.s, preferably 2.5 mPa.s to 4.0 mPa.s; (5.2) The electrical conductivity at room temperature is 8.0 mS / cm to 15 mS / cm, preferably 10 mS / cm to 15 mS / cm.
11. An electrical device, characterized in that: It comprises the negative electrode sheet according to any one of claims 1 to 7 or the sodium ion battery according to any one of claims 8 to 10.
Citation Information
Patent Citations
Negative electrode pole piece and secondary battery
CN109286020A
Lithium ion battery
CN116190565A
Negative pole piece and secondary battery
CN116364848A
Wind lithium -ion battery
CN205828579U
Carbonaceous material for non-aqueous electrolyte secondary battery anode, non-aqueous electrolyte secondary battery anode, non-aqueous electrolyte secondary battery, and vehicle
US20170149062A1